Freshwater habitats in Greece: Crosswalks between the Habitats and Water Framework Directives. Poster presentation in 11th Symposium for European Freshwater Sciences. Zagreb, June 30 – July 5, 2019 - Chrysopolitou, V.; D. Zervas; Hadjicharalampous, Ε.; Tsiaoussi, V. (2019)
Freshwater habitats are important biodiversity features in eastern Mediterranean region. Greece hosts nine freshwater habitat types of Annex I to Habitats Directive (HD); four standing and five running waters. Almost all freshwater habitats are also found in inland surface water bodies designated by the Water Framework Directive (WFD).